2013
DOI: 10.1186/1471-2164-14-s5-s6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Coffee component hydroxyl hydroquinone (HHQ) as a putative ligand for PPAR gamma and implications in breast cancer

Abstract: BackgroundCoffee contains several compounds that have the potential to influence breast cancer risk and survival. However, epidemiologic data on the relation between coffee compounds and breast cancer survival are sparse and inconsistent.ResultsWe show that coffee component HHQ has significant apoptotic effect on MDA-MB-231 and MCF-7 cells in vitro, and that ROS generation, change in mitochondrial membrane permeability, upregulation of Bax and Caspase-8 as well as down regulation of PGK1 and PKM2 expression ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…RsvE1, NPD1 and H-LA formed hydrogen bonds with the arm-I residues Hie449 (H11), Ser289(H3) and Tyr327, which are reported to be important for producing full activity of the compound by direct stabilization of H12 helix and are responsible for the transactivation activity of PPARγ [24, 31, 60, 61]. HLA also formed a hydrogen bond with Tyr473 (H12) located on the arm I that harbours transcription activation function-2(AF-2), which is obligatory for ligand binding and as well as in complimenting PPARγ function [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RsvE1, NPD1 and H-LA formed hydrogen bonds with the arm-I residues Hie449 (H11), Ser289(H3) and Tyr327, which are reported to be important for producing full activity of the compound by direct stabilization of H12 helix and are responsible for the transactivation activity of PPARγ [24, 31, 60, 61]. HLA also formed a hydrogen bond with Tyr473 (H12) located on the arm I that harbours transcription activation function-2(AF-2), which is obligatory for ligand binding and as well as in complimenting PPARγ function [27].…”
Section: Discussionmentioning
confidence: 99%
“…The ligand interactions with ARM-I side chains of Hie323 (H3), Hie449 (H11), Ser289(H3) and Tyr327 of LBD is reported to play a significant role in enhancing agonistic activity as it is found to indirectly influence the H12 stabilization [24, 31, 60, 61]. Of the 10 docked complexes, 9 bioactive lipids are predicted to act as full agonists for PPARγ by forming an H-bond interaction with the ARM-I hydrophilic cavity residues (Hie 323, Hie 449, Tyr473, Ser289 and Tyr327).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the controversial results remains unclear. Hydroxyhydroquinone inhibits the chlorogenic acid-induced restoration of endothelial function and increases production of reactive oxygen species in a dose-dependent manner [29,30]. To evaluate the effects of hydroxyhydroquinone on endothelial function, we compared the effects of coffees with a high content of chlorogenic acids and different contents of hydroxyhydroquinone in Study 1.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that hydroxyhydroquinone inhibits the chlorogenic acid-induced restoration of endothelial function in a rat model of hypertension [29]. It has also been shown that hydroxyhydroquinone increased the production of reactive oxygen species in a dose-dependent manner [30]. Some clinical studies have shown that coffee with a high content of chlorogenic acids and a low content of hydroxyhydroquinone is effective for reducing blood pressure [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator‐activated receptor gamma (PPAR‐γ) is a ligand‐activated transcriptional factor that belongs to the nuclear hormone receptor superfamily. PPAR‐γ influences the activity of several intracellular second messengers and their signaling cascade, including regulation of insulin sensitivity, glucose homeostasis, fatty acid oxidation, immune responses, redox balance, cardiovascular integrity, and cell fate . Recent studies have reported that activation of PPAR‐γ reduces the development and progression of neurodegenerative diseases by altering the expression of NF‐κB cascade .…”
Section: Ppar γ As a Therapeutic Target In Neurodegenerative Diseasesmentioning
confidence: 99%